Cancer-associated fibroblasts-induced GAS6 increases resistance to chemotherapy through AXL/STAT3/ABCG1 axis signaling pathway in gastric cancer - 김태훈 (The Graduate School, Ajou University, 2024)
Cancer-associated fibroblasts-induced GAS6 increases resistance to chemotherapy through AXL/STAT3/ABCG1 axis signaling pathway in gastric cancer. The growth arrest-specific 6 (GAS6)/AXL signaling pathway plays a crucial role in cancer-associated fibroblast (CAFs)-induced gastric cancer progression. However, the therapeutic applications of drugs targeting the interactions between GC cells and CAFs have not yet been implemented. In this study, we aimed to examine the efficacy of a novel AXL inhibitor with high selective potency to reduce CAFs-induced aggressiveness and chemoresistance in GC. The expression of GAS6 was higher in CAFs than that in other cells. Co-culture with CAFs increased AXL phosphorylation and promoted migration, downstream activation, and chemoresistance in GC cells. However, these effects decreased in CAFs treated with 9im, a small-molecule AXL inhibitor. Microarray analysis revealed that expression of ABCG1 (a key factor in the development of chemoresistance) and drug efflux increased in GC cells co-cultured with CAFs; however, 9im inhibited these effects. The STAT3 transcription factor was shown to bind to the ABCG1 promoter, and ABCG1 expression was decreased in a dose-dependent manner by the STAT3 inhibitor. Moreover, human GC tumors expressed high levels of ABCG1 and CAF markers, and their expression correlated with a worse prognosis. Overall, this study demonstrates that CAFs-derived GAS6 is a major mediator of CAFs-induced chemoresistance in GC and that GAS6/AXL/STAT3 axis signaling activates ABCG1, which may present CAFs-induced chemoresistance as a specific key mechanism. The findings suggest that a combination strategy involving chemotherapy with an AXL inhibitor may enhance the therapeutic efficacy of chemotherapy in GC treatment.
학위논문(박사)--의생명과학과,2024. 2
Keywords: Cancer-associated fibroblasts; Gastric cancer; Growth arrest-specific 6; Tumor microenvironment